Development of Solar Energy Systems Based on High Performance Bulk and Film Thermoelectric Modules - Mamykin, S.; Dzundza, B.; Shneck, R.; Vikhor, L.M.; Dashevsky, Z. (Journal of Thermoelectricity, 2025)
Due to the increase in energy demand and depletion of natural resources, the development of energy harvesting technologies becomes very important. Thermoelectric devices, based on the direct conversion of heat into electrical energy, are being the essential part of cost-effective, environmental-friendly, and fuel-saving energy sources for power generation, temperature sensors, and thermal management. High reliability and long operation time of thermoelectric energy systems lead to their extensive use in space industry and gas pipe systems. Development and wide application of solar thermoelectric converters (generators) is mainly limited by relatively low thermoelectric conversion efficiency. In this work, we suggest for the first time to use direct conversion of solar energy by systems based on high-performance multistage thermoelectric modules operating in the temperature range of 300 - 900 K for creation of autonomic systems with electric power up to 500 W and electric efficiency up to 15%. Furthermore, we developed film thermoelectric modules on thin flexible substrates with the figure of merit corresponding to that of bulk modules. Such film thermoelectric converters with output voltage of several volts and electric power of several microwatts can be used at solar energy micro-systems